The Influence of Financial Literacy, Financial Inclusion, and People’s Business Credit Financing (KUR) on The Profitability of MSMEs Among PT Pegadaian City Palembang Customers - Meileginta Kaban; Sulastri; Kemas Muhammad Husni Thamrin; Isni Andriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Sekolah Tinggi Ilmu Ekonomi Krakatau, 2025)
Purpose: This research is conducted to determine the effect of financial literacy, financial inclusion, and the People's Business Credit (KUR) financing on the profitability of MSMEs among customers of Pegadaian in Palembang City. Research Methodology: The study used 100 PT Pegadaian customers in Palembang City selected purposively. Data were collected via questionnaires and analyzed using the Statistical Package for the Social Sciences (SPSS). Results: Financial literacy shows no effect, financial inclusion negatively affects, while KUR financing positively and significantly increases MSME profitability among Pegadaian customers. Conclusions: The study found that financial literacy had no significant effect, financial inclusion negatively affected MSME profitability, while KUR financing had a positive and significant impact, emphasizing the need to strengthen literacy and inclusion programs. Limitations: The study focuses only on PT Pegadaian customers in Palembang City and examines MSME profitability based on financial literacy, inclusion, and KUR financing. Contribution: This research can contribute to providing references for further research activities, especially for researchers interested in conducting more in-depth studies in this field.